On the Causal Interpretation of Non-Triangular Systems of Economic Relations: A Rejoinder - Basmann, R. L. (Econometrica, 1963)
The Strotz-Wold Reply, however, penetrates to the heart of the issue, almost, and it will probably be illuminating to make a rejoinder. To begin with I should like to say that they are justified in taking exception to the unfortunate wording of the headnote. Though, when applied to the sequence of recipes given out by Wold, my remarks do not lack for verisimilitude, they are certainly not true to the letter of the Strotz-Wold article, and I should have taken pains not to convey the impression that I thought they were.2 Accepting their just remonstrance, I turn to the text of my article. The main contention of my paper was that the classical scientific notion of causality (not, however, the doctrine of cause and effect) 3 is adequate to rationalize the construction of non-triangular or interdependent mechanical models in economics; that employment of the classical notion in the case of non-triangular systems neither leads to paradox nor calls for novel categories of causality, e.g., circular causality, bi-causality, vector causality,